Implementasi Program Pengelolaan Lingkungan Hidup di Gereja Protestan Maluku: Kajian Ekoteologis dan Partisipasi Jemaat - Hursepuny, Jelfy Lordy; Pugesehan, Donny Japly; Nanuru, Ricardo Freedom (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
This research investigates the implementation of environmental management programs within the Maluku Protestant Church (GPM), aiming to map their execution, identify influencing factors, and analyze congregational participation. A qualitative methodology guides this research. Data collection involves an in-depth literature review of GPM's environmental programs, coupled with interviews and focus group discussions with church officials, congregation members, and local community leaders in Maluku. The collected data will be analyzed to identify relevant patterns, trends, and findings concerning program implementation. The study concludes that environmental management within the GPM is an integral part of its Christian faith responsibility to preserve God's creation. A thorough understanding of program implementation, success factors, and congregational participation is expected to contribute to creating a better and more sustainable environment, aligning with Christian teachings on earth stewardship.